Perubahan Perilaku Konsumtif dan Gaya Hidup Tenaga Kerja Wanita (TKW) Purna - Ekapti Wahjuni Djuwitaningsih (Universitas Muhammadiyah Ponorogo, 2019)
Differences in environmental cultures lead to changes in behavior and lifestyle Post-returning ex-TKW. They tend to bring the culture from abroad like consumptive behavior, and lifestyles that follow the trend, though not all so. So they forget the main purpose to fulfill the needs of the household or to open a new business, they are more concerned with personal desire to behave consumptive follow the trend. This research was conducted in Polorejo Village of Ponorogo Regency. Qualitative descriptive research method, determination of informant snow ball sampling method to ex-TKW, to search data using observation, interview and documentation with data analysis Interactive Model Analysis and data validation with triangulation method. The purpose of the study describes the Changes of Consumptive Behavior and Change of Lifestyle of Full-time Female Workers (TKW) in Polorejo Village of Ponorogo Regency. Result of research Consumptive behavior change done by TKW full is influenced by hegemony of society perception that TKW success have much money, assuming they can increase self esteem in society. As a result TKW behaved consumerism, a simple lifestyle that turned into a lifestyle that tends to follow the trend. Lifestyle changes include clothing, housing, and food. Clothing is everything in use from head to toe, whereas the housing is everything that is perceived to be a necessity like home, electronic equipment and gadgets, and the last is food that includes tastes to the habit of eating a stylish fast food modern.